Peranan Polsek Mapanget dalam Penanggulangan Kejahatan Geng Motor (Balap Liar) di Kota Manado - Ronald Andry Mauboy (Jurnal Indonesia Sosial Teknologi, 2022)
This study aims to handle conflicts that occur in the Toboko Mangga Dua Village in Ternate City, the Brimob Unit handles conflicts using a SWOT analysis which is useful for analyzing every aspect that exists in the community and the Brimob Unit in Ternate City so that conflicts in Toboko Mangga Dua Village can be resolved. immediately resolved, SWOT itself has various important roles in outlining the origin of the conflict so that it can make decisions on conflict problems that often occur and can provide good decisions in the future so that the Brimob unit of Ternate City can carry out a better handling process when dealing with the same problem. at a later time.